Effect of Pomegranate Seed Oil Encapsulated in Chitosan-capric Acid Nanogels Incorporating Thyme Essential Oil on Physicomechanical and Structural Properties of Jelly Candy - H Mirzaee Moghaddam (Ferdowsi University of Mashhad, 2021)
Pomegranate seed oil (PSO) is a well-known source of valuable compounds. The aim of this study was to investigate physicomechanical and structural properties of jelly candy enriched with PSO encapsulated in chitosan (CS)-capric acid (CA) nanogel incorporating thyme essentioal oil (TEO). For this purpose, initially the CS-CA nanogels were produced by creating amide bondes between CS and CA, which Scanning Electron Microscope (SEM) image showed the spherical form of CS-CA nanogels. Then, PSO-in-water Pickering emulsions were stabilized with the CS-CA nanogels as well as the CS-CA nanogels incorporating TEO. The results showed that the presence of TEO in the nanogel structure caused smaller oil droplets. Then, Pickering emulsions were used in the formulation of jelly candy and subsequently the microscopic structure, texture profile analysis (TPA) and color indexes of jelly candies were studied. The use of PSO in the encapsulated form reduced the separation of the PSO from the texture of the jelly candy. The results of TPA showed that although the samples containing PSO in the encapsulated form had lower hardness (156.6-173.4 N), gumminess (202.2-262.1 N), cohesiveness (1.3-1.5%), resilience (40.2-54.7 N.s) and adhesiveness (0.29-0.4 N.s) than the control (250.3 N, 627.9 N, 2.14%, 160.7 N.s, 0.63 N.s), their springiness (0.92-0.93%) was higher than the control (0.79%). Moreover, the color indexes showed that the samples containing PSO in the encapsulated form changed the color indexes more than the control, which was more in the presence of TEO.